Exogenous Calcium Delays Grape Berry Maturation in the White cv. Loureiro While Increasing Fruit Firmness and Flavonol Content - Martins, Viviana; Unlubayir, Marianne; Teixeira, António; Lanoue, Arnaud; Gerós, Hernâni (Frontiers in Plant Science, 2021)
Vineyard calcium (Ca) sprays have been increasingly used by grape growers to improve fruit firmness and thus maintain quality, particularly in periods of heavy rains and hail. The observation that Ca visibly modified berry size, texture and color in the most prominent white cultivar of the DOC region ‘Vinhos Verdes’, Loureiro, led us to hypothesize that Ca induced metabolic rearrangements that resulted in a substantial delay in fruit maturation. Targeted metabolomics by UPLC-MS and directed transcriptomics were thus combined to characterize the metabolic and transcriptional profile of cv. Loureiro berries that, together with firmness, °Brix and fruit weight measurements, allowed to obtain an integrated picture of the biochemical and structural effects of Ca in this cultivar. Results showed that exogenous Ca decreased amino acid levels in ripe berries while upregulating PAL1 expression, and stimulated the accumulation of caftaric, coutaric and fertaric acids. An increase in the levels of specific stilbenoids was observed, namely E-piceid and E-ω-viniferin, which correlated with the upregulation of STS expression. Trace amounts of anthocyanins were detected in berries of this white cultivar, but Ca treatment further inhibited their accumulation. The increased berry flavonol content upon Ca treatment confirmed that Ca delays the maturation process, which was further supported by an increase in fruit firmness and decrease in weight and °Brix at harvest. This newly reported effect may be specific of white cultivars, a topic that deserves further investigation.